(3a-4/2)-(2a+5/4)+(3/2)=0

Simple and best practice solution for (3a-4/2)-(2a+5/4)+(3/2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3a-4/2)-(2a+5/4)+(3/2)=0 equation:



(3a-4/2)-(2a+5/4)+(3/2)=0
We add all the numbers together, and all the variables
(3a-2)-(+2a+5/4)+(+3/2)=0
We get rid of parentheses
3a-2a-2-5/4+3/2=0
We calculate fractions
There is no solution for this equation

See similar equations:

| 3x+15=3x-17 | | 34=4c-6 | | 54s+36=24s+3 | | C=4.5+0.5m | | 7+17y=58 | | -1(1x-5=9 | | 6(n+3)=24 | | m+42-23=10 | | 160-w=34 | | 6(n+3)=18 | | t=0.6(220-12) | | 46.53/67=x/100 | | 155=5-v | | -7x2-11x-4=0 | | 2x=10=86=x | | 56=10^x | | 7=t/4 | | 10x-3=45 | | 12-6x=10x-13 | | 22-b=-210 | | -v+175=224 | | (1/15)(-6)=x | | 14x+15=-15x-9 | | 3(x+5)=2(-6–x)–2x | | 40p+40=8p+8 | | 9x+21x-5=6(5x+6) | | 30+5(2y-4)=40 | | 9x+21x-5=6(5x+6 | | 1/4y+3=11 | | 2(x+4=16 | | 6u2–u+1=0 | | 10x-3=3+11x |

Equations solver categories